A functional analysis of 180 cancer cell lines reveals conserved intrinsic metabolic programs. Issue 11 (2nd November 2022) - Cherkaoui, Sarah; Durot, Stephan; Bradley, Jenna; Critchlow, Susan; Dubuis, Sebastien; Masiero, Mauro Miguel; Wegmann, Rebekka; Snijder, Berend; Othman, Alaa; Bendtsen, Claus; Zamboni, Nicola
Abstract: Cancer cells reprogram their metabolism to support growth and invasion. While previous work has highlighted how single altered reactions and pathways can drive tumorigenesis, it remains unclear how individual changes propagate at the network level and eventually determine global metabolic activity. To characterize the metabolic lifestyle of cancer cells across pathways and genotypes, we profiled the intracellular metabolome of 180 pan‐cancer cell lines grown in identical conditions. For each cell line, we estimated activity for 49 pathways spanning the entirety of the metabolic network. Upon clustering, we discovered a convergence into only two major metabolic types. These were functionally confirmed by 13 C‐flux analysis, lipidomics, and analysis of sensitivity to perturbations. They revealed that the major differences in cancers are associated with lipid, TCA cycle, and carbohydrate metabolism. Thorough integration of these types with multiomics highlighted little association with genetic alterations but a strong association with markers of epithelial–mesenchymal transition. Our analysis indicates that in absence of variations imposed by the microenvironment, cancer cells adopt distinct metabolic programs which serve as vulnerabilities for therapy. Synopsis: Metabolomics and computational analysis of 180 cell lines grown under the same condition reveals the activity of over 45 metabolic pathways and identifies two major metabolic types. Metabolic activity, termed pathway scores, was inferred from metabolite levels. The emergence of only two conserved intrinsic metabolic types reveals that the major differences in the metabolism of cancers are associated with lipid and carbohydrate metabolism. Each metabolic type has a different sensitivity to gene knock‐out and drug response, matching their metabolic program which was confirmed by 13 C labeling. Omics integration reveals that the main determinant of metabolic types is their epithelial‐mesenchymal transition status. Abstract : Metabolomics and computational analysis of 180 cell lines grown under the same condition reveals the activity of over 45 metabolic pathways and identifies two major metabolic types.